Methanolic extraction and phytochemical characterisation of mature fruits of Emblica officinalis - T. R. Sreelekshmi; K.S.Prasanna None; I. S. Sajitha; S. S. Devi; S. Suja Rani; M. D. Pratheesh (Journal of Veterinary and Animal Sciences)
The study focused on the methanolic extraction of mature fruits of Emblica officinalis (amla) using the Soxhlet extraction method followed by a preliminary screening of its phytochemical content. Methanol was chosen as the solvent due to its ability to extract a wide range of polar phytochemicals. The analysis of the extract revealed the presence of several key compounds, including phenols, steroids, saponins, and tannins. These compounds are recognised for their antioxidant, anti-inflammatory and immune-modulating properties, contributing to therapeutic potential of amla. Phenols and tannins are known for their strong antioxidant activities, helping to reduce oxidative stress and prevent cellular damage. Steroids and saponins play vital roles in immune regulation and maintaining cholesterol levels. The results of this study highlight the effectiveness of methanolic extraction using the Soxhlet method in isolating these bioactive compounds from amla, supporting its use in traditional medicine and modern herbal formulations. The findings further validate the therapeutic properties of Emblica officinalis and emphasise its importance as a natural source of healthpromoting substances.